2023
DOI: 10.3389/fnins.2023.1116087
|View full text |Cite
|
Sign up to set email alerts
|

Integrative genetic and single cell RNA sequencing analysis provides new clues to the amyotrophic lateral sclerosis neurodegeneration

Abstract: IntroductionThe gradual loss of motor neurons (MNs) in the brain and spinal cord is a hallmark of amyotrophic lateral sclerosis (ALS), but the mechanisms underlying neurodegeneration in ALS are still not fully understood.MethodsBased on 75 ALS-pathogenicity/susceptibility genes and large-scale single-cell transcriptomes of human/mouse brain/spinal cord/muscle tissues, we performed an expression enrichment analysis to identify cells involved in ALS pathogenesis. Subsequently, we created a strictness measure to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 79 publications
(74 reference statements)
0
1
0
Order By: Relevance
“…Strictness refers to the spectrum of expression fold change in normal cells. Our prior research demonstrated that amyotrophic lateral sclerosis susceptibility genes with a known mechanism of loss of function (LoF) exhibit high strictness and the gain-of-function genes exhibit low strictness ( 18 ). On this premise, we calculated the strictness of susceptibility genes in monocytes and demonstrated that susceptibility genes have significantly higher strictness than LoF-tolerant (LoFT) genes ( P = 5.52 × 10 −15 ) ( Fig 1C ) and all background genes ( P = 1.13 × 10 −5 ) ( Fig 1D ), indicating that they are dosage-sensitive.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Strictness refers to the spectrum of expression fold change in normal cells. Our prior research demonstrated that amyotrophic lateral sclerosis susceptibility genes with a known mechanism of loss of function (LoF) exhibit high strictness and the gain-of-function genes exhibit low strictness ( 18 ). On this premise, we calculated the strictness of susceptibility genes in monocytes and demonstrated that susceptibility genes have significantly higher strictness than LoF-tolerant (LoFT) genes ( P = 5.52 × 10 −15 ) ( Fig 1C ) and all background genes ( P = 1.13 × 10 −5 ) ( Fig 1D ), indicating that they are dosage-sensitive.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study ( 18 ), the strictness measure was defined to estimate the dosage requirement for a given gene. Strictness was calculated by the SD of fold change: , in which S denotes strictness, C refers to fold change, i refers to the i th cell, and n refers to the total number of cells.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…76 Cell type expression enrichment analysis was performed in large-scale single-cell transcriptome datasets of liver, 37,77 heart, 78 kidney, 79 and gut 80 via EWCE 81 method described in our previous study. 82,83 P -values were adjusted by the FDR method. Adjusted P -value at a threshold of < 0.05 was used to indicate the significant enrichment.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, various in vitro cellular models with induced pluripotent stem cells (iPSCs) [166] and organoids [167] from donors with sporadic ALS show phenotypic differences in the pattern of neuronal organization and degeneration, protein aggregation, cell death, as well as in onset and progression [168]. The further development of these methods in combination with advanced omics technologies, such as single-cell sequencing and Deep Learning algorithms, will allow precise, accurate and reliable decoding of patient-specific cellular and genetic dysfunction, leading not only to an individual molecular diagnosis but a solid predictive model for applying personalized therapies [169,170].…”
Section: Predictive Modelsmentioning
confidence: 99%